Getting to grips with Postpositivism: The deliberations of a research novice - Kirby, Nicola (South African Journal of Higher Education, 2016)
As someone with a qualification in the Natural Sciences, (and a teacher on a programme offering students alternative access to university Science studies), I was ill prepared to engage with the philosophical nature of my own studies towards a postgraduate degree in Higher Education. Naively, I came across postpositivism, the emergent, contemporary form of positivism. Amid a wide range of paradigmatic stances, and apparent misunderstandings of positivism in particular, I have been forced to find my own interpretation of postpositivism. The following essay is the result of these deliberations. Critical realism is found to be a sagacious ontological position to take within postpositivism. Not only is this framework revealed to be a good opportunity to explore anti-dualistic approaches to educational research, but it is a convincing compromise in the context of a Science Faculty where the discourse is typically not relativist, and quantitative methods are hegemonic.